Modelagem de um processo térmico de dessalinização solar por umidificação e desumidificação - Bruno Lacerda de Oliveira Campos (2017)
Due to factors such as global warming, population growth and environment degradation, access to drinking water has become a problem in many regions of the planet, especially where the weather is dry. In Brazil, there is already a desalination plant in operation in Fernando de Noronha to supply the fresh water demand, besides others in a project phase in Fortaleza, Cubatão and Sergipe. Solar desalination by humidification-dehumidification is a method whose energy source is clean and renewable, and is an interesting alternative to purifying salt or brackish water for human consumption. Modeling works of this system may be divided in two groups: those that consider saturated air in the whole system and the ones that do not adopt this consideration and develop a more complex model. In this work, both strategies are proposed to the development of the models. These models have parameters to be estimated from literature experimental data. The prediction results of distillate production from both developed models present average errors 48% and 61% lower than the ones reported in literature, and the most efficient model was the one in which it was considered saturation in only one of the air streams, so that it is the recommended model for project calculations, optimization, sensibility analysis, and others. According to the sensibility analysis of distillate production in relation to input parameters, the following variations led to significant increase in distillate flow rate: increase in the effective absorbed heat in the solar collector, increase in the heights of the condenser and the humidifier, increase in the temperature of feed seawater and decrease in the feed seawater flow rate. It was verified that the joint increase in the humidification and condensation columns led to greater gain in distillate production than a single increase in one of the columns.